The Pattern of Dependence of the Aruk – Biawak Border Communities in the Middle of the COVID-19 Pandemic A global pandemic - Elyta Elyta; Ully Nuzulian; Ratu Zahirah Lutfie (Journal of Research in Social Science and Humanities, 2024)
Aruk is located on the direct border between Indonesia and Malaysia. The national border in Aruk is classified as one of the seven Integrated Border Crossing Posts. The one located in Indonesia. The following locations are integrated: Others in Entikong, Sanggau Regency, West Kalimantan; Motaain in Belu Regency, East Nusa Tenggara; Badau in Kapuas Hulu District; Motamasin in Malacca District; Wini in North Central Timor District; and Skouw in Jayapura. President Jokowi has officially inaugurated the seven borders, which are collectively known as the Seven Indonesian Borders. Aruk facilitates cross-border activities, particularly with Malaysia, thereby enhancing regional economic prospects. Conversely, the presence of this advantageous location might also result in reliance on the inhabitants of Kab. Sambas, particularly in Aruk and other regions along the Malaysian border.